THE RELATIONSHIP OF SAFETY AND HEALTH KNOWLEDGE AND ATTITUDE OF USE OF SELF-PROTECTOR EQUIPMENT WITH WORK ACCIDENT ACCIDENT IN BATIK KNIFE CRAFTS IN PT. X - Edwina Rudyarti (Universitas Darussalam Gontor, 2017)
Occupational Safety and Health (OSH) knowledge is an integral in the system of employment and human resources. Accident is undesirable and can not be known when it happened, but it can be anticipated. Attitude in the use of Personal Protective Equipment (PPE) is essential in order to reduce the incidence of workplace accidents in the industry knife batik craftsmen of PT. X. This study aims to determine the relationship of knowledge on OSH and attitudes to the use of PPE at the workplace where accident of knife batik in PT. X. Type of quantitative research, using cross sectional design. The number of research subject were 31 people. The independent variable among others, knowledge on OSH and attitudes of the use of PPE workers batik craftsmen knife. The dependent variable was the incidence of occupational accidents in the workplace of batik craftsmen knife. Measurements using a questionnaire respondents identity and scale includes 3 kinds knowledge on OSH, attitude use of PPE and work accidents in the workplace. Analyzed by univariate, bivariate, multivariate with analysis product moment Pearson correlation and linear regression. The results showed a significant correlation between knowledge on OSH at work and the attitude of the use of PPE with accidents in the workplace, where knowledge of OSH contributed 16% and the attitude of the use of PPE contributed 22% of the accidents and the attitude of the use of PPE with accidents in the workplace contributes 35.6%. There is a significant effect between knowledge on OSH and attitudes towards the use of PPE accident of knife batik craftsmen in PT. X. Keywords: Knowledge on OSH, PPE attitudes, Occupational Accident, Knife batik craftsmen.